A study of clinical and histopathological correlation of sinonasal masses - Gujrathi, Atishkumar B.; Rathod, Indutai G.; Khadkekar, Shashin; Gadpayale, Nishikant; Paikrao, Yogesh; Kamble, Paritosh A.; Kurande, Harshada; Benny, Libin Mathew (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Nasal masses are finding in an ENT (Ear, nose, throat) outpatient department. Most patient present with complaints of nasal obstruction.Other symptoms are nasal discharge, epistaxis and disturbances of smell. Sinonasal mass may be neoplastic (benign or malignant) or non-neoplastic (congenital, inflammatory) in nature. It is difficult to determine actual pathology underneath every nasal masses so, histopathological evaluation is mandatory for definitive diagnosis. Methods: The present study is prospective observational study of symptomatology, demographic profile and histopathological correlation of sinonasal masses in samplw size 80, these are the total number of patients presenting at tertiary health care centre from 1st Jan 2019 to 30th June 2020 (18 months) the study include, patients of any age and sex presenting with nasal symptoms Results: Majority of patients with sinonasal masses where in the age group 2nd decade. Male female ratio was 1.28:1. Nasal obstruction was the most common presentation. Most common non neoplastic lesion was ethmoidal polyposis and most common benign lesion was hemangioma. Most common malignant lesion was squamous cell carcinoma. Conclusions: Presenting features of all sinonasal masses may be indistinguishable and post diagnostic dilemma. Correlation of clinical and histo-pathological modalities is of utmost importance for accurate diagnosis.